First Responders While Administering Unrealized Integrated Pre-Hospital - Fitri Anita; Tita Hariyanti; Tony Suharsono (International Journal of Science and Society, 2020)
The mortality rate concerning post-traffic accident trauma is estimated to gets higher for the next years. When a traffic accident occurs, the provision of first aid is carried out by laypeople/communities around the scene with limited knowledge and equipment available. Especially, if a traffic accident occurs in an area that has not applied an integrated pre-hospital service. This research aims to explore the first responders’ care administration in a region that has not applied pre-hospitalized emergency service formally. This is a qualitative study with a case study approach. This approach is chosen to identify emerging themes. The research was conducted in Konawe municipality, from February until March 2020. It was done by interviewing 8 participants consisting of the citizens, traffic police officers, hospital party, and health agency in the research site that had been selected based on the applied inclusion criteria. Five themes were found in this research. First responders struggle to save the traffic accident victims after the incident. They helped accident victims with limited tools. They helped the accident victims by sending them off to a health service immediately. They attempt to help the victims by sending them off to health services by using public transportation. Support Police action when finding accident victims. It could be concluded that in the area that has not applied integrated-emergency pre-hospital service would directly influence service availability in the society. The people would struggle to substitute the roles of medical workers in administering the first aid outside of a hospital with various limitations. Education and training programs concerning administering first aid, given quarterly, could be an appropriate health service program to offer for broader people as the first responders.